Related Securities and Equity Market Quality: The Case of CDS - Boehmer, Ekkehart; Chava, Sudheer; Tookes, Heather E. (Journal of Financial and Quantitative Analysis, 2015)
Abstract We document that equity markets become less liquid and equity prices become less efficient when markets for single-name credit default swap (CDS) contracts emerge. This finding is robust across a variety of market quality measures. We analyze the potential mechanisms driving this result and find evidence consistent with negative trader-driven information spillovers that result from the introduction of CDS. These spillovers greatly outweigh the potentially positive effects associated with completing markets (e.g., CDS markets increase hedging opportunities) when firms and their equity markets are in “bad” states. In “good” states, we find some evidence that CDS markets can be beneficial.